2020
DOI: 10.1021/acsomega.0c03605
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Hydrothermal Preparation of Corn Straw Hydrochar as Supercapacitor Electrode Materials

Abstract: In this work, we propose the microwave-assisted hydrothermal activation method to synthesize supercapacitor electrode materials from corn straw under a small amount of the potassium catalyst (30 wt %), which can meet the environmental protection and low-cost requirement. With the extension of radiation time from 40 to 100 min, the pore structure of hydrochar expands from the micropore to hierarchical pore, and the microstructure evolves from an amorphous structure to graphene-like sheets. Microwave-assisted hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Liu et al utilized the microwave-assisted hydrothermal method to fabricate PCNS from corn straw using 30 wt % KOH microwave irradiated at 1000 W and 2450 MHz for different time intervals (40, 70, and 100 min) where the extended irradiation leads to hierarchical pores. The obtained 2D PCNS possessed excellent graphitization degrees and high SSAs of up to 1781 m 2 g –1 . Chen et al synthesized ultrathin graphene sheets (2–10 atomic layers) with interlayer spacings of 0.3362 nm through hydrothermal and graphitization processes utilizing wheat straw as a precursor .…”
Section: Synthetic Methods For 2d Pcnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al utilized the microwave-assisted hydrothermal method to fabricate PCNS from corn straw using 30 wt % KOH microwave irradiated at 1000 W and 2450 MHz for different time intervals (40, 70, and 100 min) where the extended irradiation leads to hierarchical pores. The obtained 2D PCNS possessed excellent graphitization degrees and high SSAs of up to 1781 m 2 g –1 . Chen et al synthesized ultrathin graphene sheets (2–10 atomic layers) with interlayer spacings of 0.3362 nm through hydrothermal and graphitization processes utilizing wheat straw as a precursor .…”
Section: Synthetic Methods For 2d Pcnsmentioning
confidence: 99%
“…On the basis of the pore diameter, they can be classified into microporous (pore size < 2 nm), mesoporous (2 nm < pore size < 50 nm), and/or macroporous (pore size > 50 nm) carbons . Their applicability in the above-mentioned fields is not only due to their superior chemical and physical properties like high thermal and electrical conductivity, good chemical stability, and low density but also due to the ease of availability. , However, the porous carbons, which are prepared by the carbonization of polymer or biomass precursors and the following activation always have complicated and uncontrollable porous structure, resulting in low surface utilization and very large mass transfer resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The authors have suggested that the microwave irradiation not only increases the rate of the hydrolysis reaction, which is signicant for the depolymerization and rearrangement of the precursor carbon skeleton, but also offers a graphitization effect by facilitating the motion of the catalyst (potassium; 30 wt%) in between the carbon layers. 161 Likewise, P, N-rich agricultural (rapeseed) and antibiotic (lincomycin) residual feedstocks were used for the preparation of hydrochars via microwave-assisted HTC method for environmental applications. 162 The advantages of HTC process over pyrolysis include improved energy consumption, minimized toxic wastes generation, higher yield ($30-60 wt%), retention of surface hydroxyl and carboxylic functional groups and doping of heteroatoms.…”
Section: Hydrothermal Carbonization (Htc)mentioning
confidence: 99%
“…Liu et al proposed a microwave-aided hydrothermal activation method to fabricate supercapacitor electrode materials using corn stover with the presence of potassiumbased catalyst. 22 Dried corn stover and potassium hydroxide powders in a weight ratio of 2:1 are put in a hydrothermal tank and mixed with deionized water, as shown in Figure 5a. The reaction tank is put into a microwave reactor, heated at 1000 W and 2450 MHz, and held for 40, 70, and 100 min, respectively.…”
Section: ■ Corn-mediated Carbonaceous Materials As Porous Electrodes ...mentioning
confidence: 99%
“…(e–g) TEM images of the hydrochar sample made with radiation times of 40, 70, and 100 min, respectively. Adapted with permission from ref . Copyright 2020 American Chemical Society.…”
Section: Corn-mediated Carbonaceous Materials As Porous Electrodes In...mentioning
confidence: 99%